Bacterial formate hydrogenlyase complex - McDowall, Jennifer S. (National Academy of Sciences, 2014)
Under anaerobic conditions, Escherichia coli can carry out a mixed-acid fermentation that ultimately produces molecular hydrogen. The enzyme directly responsible for hydrogen production is the membrane-bound formate hydrogenlyase (FHL) complex, which links formate oxidation to proton reduction and has evolutionary links to Complex I, the NADH:quinone oxidoreductase. Although the genetics, maturation, and some biochemistry of FHL are understood, the protein complex has never been isolated in an intact form to allow biochemical analysis. In this work, genetic tools are reported that allow the facile isolation of FHL in a single chromatographic step. The core complex is shown to comprise HycE (a [NiFe] hydrogenase component termed Hyd-3), FdhF (the molybdenum-dependent formate dehydrogenase-H), and three iron-sulfur proteins: HycB, HycF, and HycG. A proportion of this core complex remains associated with HycC and HycD, which are polytopic integral membrane proteins believed to anchor the core complex to the cytoplasmic side of the membrane. As isolated, the FHL complex retains formate hydrogenlyase activity in vitro. Protein film electrochemistry experiments on Hyd-3 demonstrate that it has a unique ability among [NiFe] hydrogenases to catalyze production of H(2) even at high partial pressures of H(2). Understanding and harnessing the activity of the FHL complex is critical to advancing future biohydrogen research efforts.